2016
DOI: 10.1007/s10068-016-0217-1
|View full text |Cite
|
Sign up to set email alerts
|

Strategies in fed-batch cultivation on the production performance of Lactobacillus salivarius I 24 viable cells

Abstract: The potential use of fed-batch cultivation (FBC) for improvement of the production of I 24 biomass for subsequent use as probiotics was studied using a 2-L stirredtank bioreactor. Three different constant feeding rates (0.1, 0.05, and 0.033 L/h) were applied in FBCs and their effect on carbon metabolism was evaluated. The carbon flux for cell built-up with reduction in lactic acid synthesis was observed in the fed-batch as compared to the batch cultivation mode. The viable cell number obtained in the constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Reduced viable cell concentration with increased glucose concentration was due to high lactic acid accumulation in the culture since P. acidilactici undergo homofermentation. Generally, lactic acid conversion rate from sugar surpass 80% of the theoretical yield for homofermentative bacteria (Liu et al 2013 ) and fermentation in lactobacilli tends to redirect its carbon flux from cell built-up to lactic acid production (Ming et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced viable cell concentration with increased glucose concentration was due to high lactic acid accumulation in the culture since P. acidilactici undergo homofermentation. Generally, lactic acid conversion rate from sugar surpass 80% of the theoretical yield for homofermentative bacteria (Liu et al 2013 ) and fermentation in lactobacilli tends to redirect its carbon flux from cell built-up to lactic acid production (Ming et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the fermentations, 5 mL of culture samples were withdrawn at time intervals for analysis. Cell growth was determined using colony forming unit (CFU) (Ming et al 2016 ). Samples were serially diluted (10 3 –10 10 ) with 0.9% (w/v) sterile saline water (NaCI) and plated onto MRS agar plate.…”
Section: Methodsmentioning
confidence: 99%
“…In 2003, Schiraldi et al [ 80 ] suggested a dire need to develop efficient strategies enabling maintaining lactate concentration in the culture at below toxic level. In literature, we can find some examples of fed-batch fermentation as a method useful to overcome the end-product inhibition in LAB fermentation [ 82 , 83 , 84 ]. However, it appears that this methodology is often inefficient due to high osmotic pressure excided 2416 mOsm kg −1 and accumulation of acid anions and various metabolites [ 85 ].…”
Section: Toxicity Against Microorganismsmentioning
confidence: 99%
“…The development of fermentation strategies that can maintain lactate concentration in the culture at below toxic level will be beneficial to overcome the product inhibition ( Schiraldi et al, 2003 ). There are numerous reports on fed-batch fermentation that were conducted to overcome the end product inhibition in LAB fermentation which in turn enhanced biomass production ( Boon et al, 2007 ; Aguirre-Ezkauriatza et al, 2010 ; Ming et al, 2016 ). However, the use of fed-batch and pH controlled fermentations for overcoming end product inhibition in LAB fermentations are often inefficient due to high osmotic pressure and the presence of acid anions ( Cui et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%